From the figure of the Media Ombudsman to the singularities of the Ombudsman Paquete de Oliveira - Oliveira, Madalena (2017)
Inherited from the public administration and politics, the position of the media ombudsman corresponds essentially to an instrument of self-regulation that invites the public itself to participate in the process of critical reflection on the media and its practices. Adopting in Portugal the specific name of provedor, this position has been understood as consisting in a mediator between the media and the correspondent audiences. Although some approaches tend to see in the ombudsman an activity of marketing of the media companies (a kind of “customers service”), in its origin this function is linked to the need to understand the perceptions of readers, listeners and viewers on the performance of the media and their professionals and contribute to promote a critical awareness of media role in society.The media ombudsman experience has in Portugal a 20 year-old history. It began in the press and was extended to public service audiovisual media in 2006. Although not all media companies have “subscribed” the initiative to incorporate this function, since 1997, in the press, radio and television, two dozens of ombudsmen were already assigned. Without pretending to do an exhaustive analysis, this article focuses on the purpose of reflecting in general terms not only on the function itself but also on the profile of the one who assumes it. This is the opportunity to take as a reference the inaugural experience of the TV ombudsman, repeated later in the newspaper Público, to appreciate the singularities of the ombudsman Paquete de Oliveira.